2016
DOI: 10.1093/alcalc/agv142
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical Characteristics, and Risk Factors for Non-recording of Alcohol Use in Hospitals across Europe: The ALCHIMIE Study

Abstract: A considerable proportion of medical patients admitted in European hospitals fulfill criteria for alcohol use disorders. These patients are frequently overlooked during hospitalization and not appropriately registered in medical records. Women, older patients, and inpatients from European areas with high local alcohol use prevalence are at higher risk associated with a non-recording of alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…One in five inpatients surveyed reported risky drinking behaviours. This is higher than the 16% reported by the European cross‐country study [30], but is comparable to recently reported, Australian national prevalence of risky drinking of approximately 22% [38]. While it could be presumed that hospital inpatient populations would have greater alcohol burden than the general public, especially in our health service which has statewide services such as major trauma and psychiatric intensive care, these figures may have been diluted by our subacute, geriatric hospital campuses which have a skewed demographic profile of females over 70 years (however no significant difference in risky drinking by hospital campus was found).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…One in five inpatients surveyed reported risky drinking behaviours. This is higher than the 16% reported by the European cross‐country study [30], but is comparable to recently reported, Australian national prevalence of risky drinking of approximately 22% [38]. While it could be presumed that hospital inpatient populations would have greater alcohol burden than the general public, especially in our health service which has statewide services such as major trauma and psychiatric intensive care, these figures may have been diluted by our subacute, geriatric hospital campuses which have a skewed demographic profile of females over 70 years (however no significant difference in risky drinking by hospital campus was found).…”
Section: Discussioncontrasting
confidence: 65%
“…Currently, the true burden of high‐risk alcohol use and dependence among inpatients in Australia is not well‐established. A recent European cross‐country study screening 2100 inpatients from 43 hospitals in 8 European countries using the AUDIT‐C (and subsequently the full AUDIT and clinical evaluation for those who screened positive on the AUDIT‐C), reported 16% ( n = 346) fulfilled the World Health Organization criteria for either current or past AUD [30]. Several Australian studies have assessed alcohol use among both general [31,32] and specialised inpatient settings [33,34] using the AUDIT, but contemporary data on Australian general inpatient populations are lacking and premature screening program rollouts could overburden staff, leaving patients at risk.…”
Section: Introductionmentioning
confidence: 99%
“…First, it has to be considered that the information on alcohol and cigarette smoking was selfreported and may be subject to underreporting bias. Second, we should bear in mind that alcohol consumption may be under-recorded in PHC medical records, as has been described previously in a study of 9 European general hospitals [37]. From the total sample of patients with information on alcohol consumption registered in the electronic medical record, it was recorded that only 32% were considered drinkers, which is clearly below the national prevalence figures [38].…”
Section: Discussionmentioning
confidence: 98%
“…Between 15% and 30% of hospitalized patients have an alcohol-related condition ( 183 185 ). For many, treatment of the primary diagnosis necessitating hospitalization (e.g., infection, trauma, organ failure, etc.)…”
Section: Section 2: Translation Of Research To Patients (T 2 Research)mentioning
confidence: 99%
“…Treatment studies use various CIWA-Ar thresholds (of 8–20) to initiate pharmacotherapy and monitoring for patients at evaluation intervals ranging from every 10 minutes to four times daily ( 177 , 178 , 185 ). No study has documented a relationship between the frequency of assessments and patient outcomes.…”
Section: Section 2: Translation Of Research To Patients (T 2 Research)mentioning
confidence: 99%